Psychological contract, motivation, perceived supervisor support and monitoring : relationships with effort - Hu, Sheena Min En (2008)
This research project studies the factors influencing employees' effort at the workplace. It examines the two dimensions of psychological contract, namely psychological contract obligations and psychological contract inducements on effort. Specifically, it also studies the impacts of a) perceived employer inducement due to pay and b) perceived employer inducement due to support on the different types of employee motivation (intrinsic motivation, extrinsic motivation and amotivation) and perceived supervisor support, which may in turn affect employees' effort at work. Other determinants of effort like psychological contract breach and monitoring were also included in our proposed model.